Irreversible and reversible pore formation by polymeric alkylpyridinium salts (poly-APS) from the sponge Reniera sarai - McClelland, D (2003)
1. In this study, we investigated the electrophysiological actions of a high molecular weight fraction, predominantly containing two polymeric 1,3-alkylpyridinium salts (poly-APS) of 5.5 and ∼19 kDa isolated from the marine sponge Reniera sarai. The biological properties of poly-APS are of particular interest because this preparation may be used to deliver macromolecules into the intracellular environment without producing long-term damage to cells. Poly-APS (50–0.05 μg ml(−1)) was applied to cultured dorsal root ganglion neurones or HEK 293 cells and changes in cell membrane properties were measured using whole-cell patch-clamp recording and fura-2 Ca(2+) imaging. 2. Poly-APS (50 μg ml(−1)) evoked irreversible depolarisations in membrane potential and reductions in input resistance. However, doses of 5 μg ml(−1) and less produced reversible effects on these cell membrane characteristics and on Ca(2+) permeability. 3. At 0.05 μg ml(−1), poly-APS could robust transient increases in Ca(2+) permeability without damaging the neurones or subsequently attenuating Ca(2+) entry through voltage-activated channels. 4. Bathing cells in NaCl-based extracellular medium containing 1.5 mM zinc attenuated the irreversible and reversible effects of poly-APS on membrane properties (membrane potential, input resistance and whole-cell currents). In both DRG neurones and HEK 293 cells, zinc attenuated Ca(2+) entry evoked by poly-APS. These effects of zinc were only observed if zinc was continually present during poly-APS application. However, zinc failed to attenuate the actions of poly-APS if it was applied after the sponge toxin preparation had evoked changes in membrane properties. 5. In conclusion, the pore-forming preparation poly-APS can have dose-dependent interactions with cell membranes and at low doses these can be reversible. Additionally, the interactions between poly-APS and cell membranes could be attenuated by zinc.